Negative pole piece, secondary battery and electric device

By controlling specific parameter relationships in the negative electrode sheet of the lithium-ion battery, the problem of volume expansion of the silicon-based negative electrode material during charging and discharging is solved, the first-time Coulomb efficiency of the battery is improved, the impedance is reduced, and the cycle performance is significantly improved.

CN119786527AActive Publication Date: 2025-04-08ZHEJIANG LIWINON ENERGY TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411978654.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

The volume expansion of the silicon-based anode material of existing lithium-ion batteries during charging and discharging leads to electrolyte consumption and active lithium loss, resulting in poor cycle life, serious gas production at high temperature storage, and increased impedance.

Method used

By controlling the Dv50 particle size of the first negative electrode active material, the Dv50 particle size of the second negative electrode active material, the grading ratio (X) of the negative electrode active material, the tensile strength of the negative electrode sheet and the content of the binder in the negative electrode active material layer, a specific relationship is satisfied (0.69≤(A+B)*X/(N*C)≤160) to improve the adhesion and conductivity of the negative electrode sheet and suppress the expansion and contraction of the negative electrode active material.

Benefits of technology

It effectively improves the first Coulomb efficiency of the secondary battery, reduces impedance, improves cycling performance, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005221012660000131
    Figure BDA0005221012660000131
  • Figure BDA0005221012660000141
    Figure BDA0005221012660000141
  • Figure BDA0005221012660000151
    Figure BDA0005221012660000151
Patent Text Reader

Abstract

The invention discloses a negative pole piece, a secondary battery and an electric device, and belongs to the technical field of batteries. The Dv50 particle sizes of the first negative electrode active material and the second negative electrode active material in the negative electrode active materials, the grading ratio (X) of the negative electrode active materials, the tensile strength of the negative electrode plate and the content of the binder in the negative electrode active material layer are controlled to meet the following relation: (A + B) * X / (N * C) is more than or equal to 0.69 and less than or equal to 160, so that the adhesion and the conductivity of the negative electrode plate can be effectively improved; the expansion and shrinkage of the negative electrode active material are effectively inhibited, so that the stability of the negative electrode active material is improved, the negative electrode active material is uniformly distributed on the negative electrode plate, the migration and diffusion path of lithium ions on the negative electrode active material is shortened, the impedance is reduced, and the cycle performance is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a negative electrode sheet, a secondary battery and an electrical device. Background Art

[0002] With the development of information industry and electronic technology, new requirements have been put forward for battery power sources. Compared with other secondary battery systems, lithium-ion batteries have the advantages of low self-discharge, high energy density, high operating voltage, long cycle life and environmental friendliness. They meet the development needs of green batteries and have become a research hotspot in recent years.

[0003] Silicon-based negative electrode materials have attracted widespread attention from researchers due to their high specific capacity and high voltage platform. However, in the actual commercialization process, the volume expansion of the silicon negative electrode during charging and discharging, which leads to electrolyte consumption and active lithium loss, will cause the battery to face problems such as poor cycle life, severe gas generation during high-temperature storage, and increased impedance during use.

[0004] In view of this, this application is filed. Summary of the invention

[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a negative electrode plate, a secondary battery and an electrical device, which effectively improve the initial coulomb efficiency of the secondary battery, reduce impedance and improve cycle performance.

[0006] To achieve the above object, the technical solution adopted by the present invention is:

[0007] To achieve the above-mentioned object, the first aspect of the present application provides a negative electrode sheet, comprising a negative electrode current collector and a negative electrode active material layer located on at least one surface of the negative electrode current collector, wherein the negative electrode active material layer comprises a negative electrode active material and a first binder;

[0008] The negative electrode active material includes a first negative electrode active material and a second negative electrode active material;

[0009] The negative electrode sheet satisfies: 0.69≤(A+B)*X / (N*C)≤160, X=A / B;

[0010] A μm is the Dv50 particle size of the first negative electrode active material;

[0011] Bμm is the Dv50 particle size of the second negative electrode active material;

[0012] N MPa is the tensile strength of the negative electrode plate;

[0013] C% is the mass percentage of the first binder in the negative electrode active material layer.

[0014] As an implementation scheme of the present application, at least one of the following (1) to (5) is satisfied:

[0015] (1) 0.4≤A≤8;

[0016] (2) 10≤B≤45;

[0017] (3) 0.01≤X≤0.8;

[0018] (4) 0.1≤N≤0.5;

[0019] (5)0.05≤C≤10.

[0020] As an embodiment of the present application, the first binder includes at least one of polytetrafluoroethylene or its derivatives, polyvinylidene fluoride or its derivatives, carboxymethyl cellulose or its derivatives, nitrocellulose or its derivatives, styrene-butadiene rubber or its derivatives, nitrile rubber or its derivatives, and polyacrylic acid or its derivatives.

[0021] As an embodiment of the present application, the mass percentage of the first negative electrode active material in the negative electrode active material layer is D, 1%≤D≤30%; and / or

[0022] The mass percentage of the second negative electrode active material in the negative electrode active material layer is E, and 60%≤E≤98.9%.

[0023] As an implementation scheme of the present application, the negative electrode active material includes a core and a coating layer arranged on the outer surface of the core, the core includes a silicon-based material and graphite, and the coating layer includes a second binder and a conductive agent; the mass ratio of the silicon-based material, graphite, second binder, and conductive agent is (1~30): (69.4~95): (0.3~3): (0.1~1).

[0024] As an implementation scheme of the present application, the coating layer includes polyacrylic acid or its derivatives, styrene-butadiene rubber or its derivatives, carboxymethyl cellulose or its derivatives, and a conductive agent; the mass ratio of the silicon-based material, graphite, polyacrylic acid or its derivatives, styrene-butadiene rubber or its derivatives, carboxymethyl cellulose or its derivatives, and the conductive agent is (1-30): (69.4-95): (0.1-1): (0.1-1): (0.1-1): (0.1-1).

[0025] As an embodiment of the present application, the silicon-based material includes at least one of a silicon-oxygen material and a silicon-carbon material.

[0026] As an embodiment of the present application, the conductive agent includes at least one of carbon nanotubes, carbon black, carbon dots, graphene, and carbon nanofibers.

[0027] As an embodiment of the present application, the second binder includes at least one of polytetrafluoroethylene or its derivatives, polyvinylidene fluoride or its derivatives, carboxymethyl cellulose or its derivatives, nitrocellulose or its derivatives, styrene-butadiene rubber or its derivatives, nitrile rubber or its derivatives, and polyacrylic acid or its derivatives.

[0028] A second aspect of the present application provides a secondary battery, comprising the negative electrode plate described above.

[0029] A third aspect of the present application provides an electrical device, comprising the secondary battery described above.

[0030] The beneficial effects of the present invention are as follows: by controlling the Dv50 particle size of the first negative electrode active material and the second negative electrode active material in the negative electrode active material, the grading ratio (X) of the negative electrode active material, the tensile strength of the negative electrode plate and the content of the binder in the negative electrode active material layer to satisfy the following relationship: 0.69≤(A+B)*X / (N*C)≤160, the present invention can effectively improve the adhesion and conductivity of the negative electrode plate, effectively inhibit the expansion and contraction of the negative electrode active material, improve the ion conductivity of the negative electrode plate, improve the dispersion effect of the binder, avoid its agglomeration, and at the same time improve the stability of the negative electrode active material, avoid the pulverization of the plate, avoid its breakage during the preparation of the negative electrode plate, increase the compaction density, promote the uniform distribution of the negative electrode active material on the negative electrode plate, shorten the migration and diffusion path of the active ions in the negative electrode active material, effectively improve the first coulomb efficiency of the secondary battery, reduce the impedance, and improve the cycle performance. DETAILED DESCRIPTION

[0031] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.

[0032] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0033] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0034] In the present application, there is no particular limitation on the specific dispersion and stirring treatment methods.

[0035] Unless otherwise specified, the components, raw materials or instruments used in the embodiments and comparative examples of the present invention are all commercially available raw materials or instruments, and the components and raw materials used in each parallel experiment are all of the same kind.

[0036] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of the present invention, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0037] The inventors of the present application have found that the existing dry-process negative electrode sheets are prepared by fiberizing a mixed powder of active materials, conductive agents and binders, rolling them to form a self-supporting film, and then compounding them with a current collector to finally form a dry-process electrode sheet. The binder reacts with the lithium ions on the surface of the negative electrode to generate lithium fluoride, which weakens the bonding effect, reduces the capacity of the secondary battery, and seriously affects the cycle stability of the battery. It is also difficult to suppress the expansion of the silicon negative electrode, resulting in the collapse of the electrode conductive network and the bonding network due to the expansion of silicon during the recharging and discharging process of the secondary battery cell, the electrode sheet becoming pulverized, and the secondary battery cell failing.

[0038] Therefore, based on the above problems, the embodiment of the present application provides a negative electrode sheet, including a negative electrode current collector and a negative electrode active material layer located on at least one surface of the negative electrode current collector, wherein the negative electrode active material layer includes a negative electrode active material and a first binder;

[0039] The negative electrode active material includes a first negative electrode active material and a second negative electrode active material;

[0040] The negative electrode sheet satisfies: 0.69≤(A+B)*X / (N*C)≤160, for example, it can be 0.69, 0.7, 1, 2, 4, 5, 6, 10, 20, 30, 40, 50, 60, 70, 80, 90, 100, 110, 120, 130, 140, 150, 160 or a range consisting of any two values ​​therein, X=A / B;

[0041] A μm is the Dv50 particle size of the first negative electrode active material;

[0042] Bμm is the Dv50 particle size of the second negative electrode active material;

[0043] N MPa is the tensile strength of the negative electrode plate;

[0044] C% is the mass percentage of the first binder in the negative electrode active material layer.

[0045] The inventors of the present application have found that the performance of the negative electrode sheet is significantly correlated with the Dv50 particle size of the negative electrode active material, the grade ratio (X) of the negative electrode active material, the tensile strength of the negative electrode sheet, and the content of the binder in the negative electrode active material layer. The present application controls the Dv50 particle size of the first negative electrode active material and the second negative electrode active material in the negative electrode active material, the grade ratio (X) of the negative electrode active material, the tensile strength of the negative electrode sheet, and the content of the binder in the negative electrode active material layer to satisfy the following relationship: 1.5≤(A+B)*X / (N*C)≤5, It can effectively improve the adhesion and conductivity of the negative electrode sheet, effectively inhibit the expansion and contraction of the negative electrode active material, improve the ion conductivity of the negative electrode sheet, improve the dispersion effect of the binder, avoid its agglomeration, reduce the amount of lithium fluoride generated on the surface of the negative electrode sheet, and at the same time improve the stability of the negative electrode active material, avoid the pulverization of the sheet, promote the uniform distribution of the negative electrode active material on the negative electrode sheet, shorten the migration and diffusion path of the active ions in the negative electrode active material, effectively improve the first coulomb efficiency of the secondary battery, reduce the impedance, and improve the cycle performance.

[0046] Among them, the volume average particle size Dv50 of the first negative electrode active material and the second negative electrode active material has a well-known meaning in the art, which indicates the particle size corresponding to when the cumulative volume distribution percentage of the material reaches 50%, and can be tested by instruments and methods well-known in the art, for example, using a cross-section polisher (such as the IB-09010CP argon ion cross-section polisher of JEOL Corporation) to prepare a cross-section containing the first negative electrode active material and the second negative electrode active material; then, EDX or EDS elemental analysis is combined with TEM or SEM (such as the X-Max EDS of the Oxford Instruments Group in the UK combined with the Sigma-02-33 SEM of ZEISS in Germany) surface scanning test to obtain an element distribution map in the cross-section; the volume average particle size Dv50 of the first negative electrode active material and the second negative electrode active material is obtained according to the particle size distribution of the cross-section. More precisely, the volume average particle size Dv50 value of the negative electrode active material at multiple (more than 3, such as 8, 10, 12, etc.) different positions on the cross section can be tested, and the average value can be recorded as the volume average particle size Dv50 of the first negative electrode active material and the second negative electrode active material.

[0047] In one embodiment, 1.6≤(A+B)*X / (N*C)≤9.6, especially when (A+B)*X / (N*C) is controlled within this range, the impedance of the secondary battery can be further reduced and the cycle performance of the secondary battery can be improved.

[0048] In one embodiment, 0.4≤A≤8, for example, it can be 0.4, 0.5, 1, 2, 3, 4, 5, 6, 7, 8 or a range consisting of any two of these values.

[0049] In one embodiment, 1≤A≤8.

[0050] In one embodiment, 10≤B≤45, for example, it can be 10, 12, 14, 15, 18, 20, 22, 24, 25, 26, 28, 30, 35, 40, 45 or a range consisting of any two of the values.

[0051] In one embodiment, 10≤B≤30.

[0052] By controlling A and B within the above range, the wettability of the electrolyte to the negative electrode active material can be effectively improved, and the negative electrode active material can be more fully contacted with the electrolyte to form more active sites, thereby alleviating the volume expansion caused by lithium ion insertion / deinsertion.

[0053] In one embodiment, 0.01≤X≤0.8, for example, it can be 0.01, 0.03, 0.033, 0.04, 0.05, 0.08, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8 or a range consisting of any two of the values, and the particle pores of the negative electrode active material are filled to the maximum extent, which effectively improves the compaction density of the negative electrode active material, improves the wettability of the electrolyte to the negative electrode active material, effectively reduces interfacial side reactions, reduces the gas production of the secondary battery, effectively reduces the impedance of the secondary battery, and improves the cycle performance of the secondary battery.

[0054] In one embodiment, 0.033≤X≤0.8.

[0055] In one embodiment, 0.1≤N≤0.5, for example, it can be 0.1, 0.2, 0.3, 0.4, 0.5 or a range consisting of any two of these values. By controlling the tensile strength of the negative electrode plate within this range, the stability of the negative electrode plate can be effectively improved, ensuring the formation of a good conductive network, maintaining good electron transmission capabilities between the carbon-based material and graphite, and shortening the diffusion path of lithium ions, thereby effectively improving the cycle performance of the secondary battery.

[0056] Wherein, the tensile strength of the negative electrode plate is tested using a tensile tester.

[0057] Test method: speed 20mm / min, spacing 50mm, sample width 4mm, thickness P.

[0058] Calculation method: Tensile strength: N = tension F / (0.004*P).

[0059] In one embodiment, 0.1≤C≤10, for example, it can be 0.1, 0.2, 0.5, 0.8, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10 or a range consisting of any two of these values. By controlling C within this range, the conductivity and processing performance of the negative electrode sheet can be effectively improved, the expansion and contraction of the negative electrode active material can be effectively inhibited, and the cycle performance of the secondary battery can be effectively improved.

[0060] In one embodiment, the first binder includes at least one of polytetrafluoroethylene or its derivatives, polyvinylidene fluoride or its derivatives, carboxymethyl cellulose or its derivatives, nitrocellulose or its derivatives, styrene-butadiene rubber or its derivatives, nitrile rubber or its derivatives, and polyacrylic acid or its derivatives.

[0061] In one embodiment, the mass percentage of the first negative electrode active material in the negative electrode active material layer is D, 1%≤D≤30%; for example, it can be 1%, 2%, 3%, 5%, 8%, 10%, 12%, 15%, 18%, 20%, 22%, 25%, 28%, 30% or a range consisting of any two of the values.

[0062] In one embodiment, the mass percentage of the second negative electrode active material in the negative electrode active material layer is E, 60%≤E≤98.9%. For example, it can be 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, 98%, 98.9% or a range consisting of any two of these values.

[0063] In one embodiment, the negative electrode active material includes a core and a coating layer arranged on the outer surface of the core, the core includes a silicon-based material and graphite, and the coating layer includes a second binder and a conductive agent; the mass ratio of the silicon-based material, graphite, second binder, and conductive agent is (1-30): (69.4-95): (0.3-3): (0.1-1). By coating the outer surface of the negative electrode active material with the coating layer containing the binder and the conductive agent, the addition of the conductive agent can avoid agglomeration of the conductive agent and the first binder, avoid uneven dispersion, improve the dispersibility of the conductive agent and the first binder in the negative electrode sheet, effectively improve the stability of the negative electrode active material, improve the conductivity and adhesion of the negative electrode active material, effectively avoid expansion and contraction of the negative electrode active material, and improve the cycle stability of the secondary battery.

[0064] In one embodiment, the coating layer includes polyacrylic acid or its derivatives, styrene-butadiene rubber or its derivatives, carboxymethyl cellulose or its derivatives, and a conductive agent; the mass ratio of the silicon-based material, graphite, polyacrylic acid or its derivatives, styrene-butadiene rubber or its derivatives, carboxymethyl cellulose or its derivatives, and the conductive agent is (1-30): (69.4-95): (0.1-1): (0.1-1): (0.1-1): (0.1-1), especially when such a coating layer is used, the polyacrylic acid or its derivatives, styrene-butadiene rubber or its derivatives, carboxymethyl cellulose or its derivatives, and the conductive agent are coated on the negative electrode active material. The surface can improve its conductive adhesion. In the subsequent mixing process with the first binder, it can reduce the amount of the first binder added and avoid the agglomeration problem of the first binder and the conductive agent. While further improving the initial effect of the negative electrode plate, it avoids the agglomeration problem in the mixing process. Moreover, since the surface of the active material is coated with rigid adhesives such as polyacrylic acid, styrene-butadiene rubber, and carboxymethyl cellulose, under the joint action of the first binder, the dry particles and the particles are more closely contacted, the ion transmission distance is shortened, and the battery charging time is shortened. In addition, the plate can not only inhibit the expansion of silicon, but also solve the problem of plate pulverization, thereby improving the cycle stability of the battery.

[0065] In one embodiment, the silicon-based material includes at least one of a silicon-oxygen material and a silicon-carbon material.

[0066] In one embodiment, the silicon-based material includes at least one of silicon, silicon-carbon composite, and SiO.

[0067] In one embodiment, the conductive agent includes at least one of carbon nanotubes, carbon black, carbon dots, graphene, and carbon nanofibers.

[0068] In one embodiment, the second binder includes at least one of polytetrafluoroethylene or its derivatives, polyvinylidene fluoride or its derivatives, carboxymethyl cellulose or its derivatives, nitrocellulose or its derivatives, styrene-butadiene rubber or its derivatives, nitrile rubber or its derivatives, and polyacrylic acid or its derivatives.

[0069] Exemplarily, the method for preparing the negative electrode active material comprises the following steps:

[0070] The silicon negative electrode material and graphite are mixed uniformly to obtain a mixture, the mixture is mixed uniformly with a second binder and a conductive agent to obtain a precursor, the precursor is added with water to be prepared into a slurry with a solid content of 20-60%, atomized and granulated at 150-200°C, and ball milled and sieved to obtain a negative electrode active material and a second negative electrode active material (by controlling the aperture size of the atomizer for atomization and granulation and the ball milling and sieving steps, negative electrode active materials with different Dv50 can be obtained).

[0071] In one embodiment, the secondary battery further includes a positive electrode plate.

[0072] In one embodiment, the positive electrode plate includes a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, and the positive electrode active material layer includes a positive electrode active material.

[0073] In one embodiment, the positive electrode active material may be a positive electrode active material for a secondary battery known in the art. As a non-limiting example, the positive electrode active material may include a lithium-containing phosphate, a lithium transition metal oxide, and their respective modified compounds. However, the present application is not limited to these materials or substances, and other traditional materials or substances that can be used as positive electrode active materials for secondary batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, non-limiting examples of lithium transition metal oxides may include, but are not limited to, one or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and their modified compounds.

[0074] In one embodiment, the type of the positive electrode current collector is not particularly limited, and it can be any known material suitable for use as a positive electrode current collector. In one embodiment, the positive electrode current collector includes metal materials such as aluminum, stainless steel, nickel plating, titanium, tantalum, and carbon materials such as carbon cloth and carbon paper.

[0075] There is no particular restriction on the form of the positive electrode current collector. When the positive electrode current collector is a metal material, the positive electrode current collector may be in the form of metal foil, metal cylinder, metal strip roll, metal plate, metal foil, metal plate mesh, stamped metal, foamed metal, etc. When the positive electrode current collector is a carbon material, the positive electrode current collector may include but is not limited to a carbon plate, a carbon film, a carbon cylinder, etc.

[0076] In one embodiment, the positive electrode active material layer further includes a positive electrode conductor and a positive electrode binder.

[0077] In one embodiment, the type of the positive electrode conductive agent mentioned in the present application is not limited, and any known positive electrode conductive agent can be used.

[0078] In one embodiment, the positive electrode conductive agent includes at least one of carbon materials such as superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0079] In one embodiment, the positive electrode binder mentioned in this application.

[0080] In one embodiment, the positive electrode binder includes at least one of polyvinylidene fluoride, polytetrafluoroethylene, vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylate resin, polyethylene, polypropylene, polyethylene terephthalate, polymethyl methacrylate, polyimide, aromatic polyamide, cellulose, nitrocellulose, styrene-butadiene rubber, nitrile rubber, fluororubber, isoprene rubber, polybutadiene rubber, and ethylene-propylene rubber.

[0081] In the secondary battery mentioned in the present application, a separator is usually provided between the positive electrode and the negative electrode to prevent short circuit. The material and shape of the separator are not particularly limited as long as the effect of the present application is not significantly impaired.

[0082] In one embodiment, the separator includes a porous sheet or non-woven fabric having excellent liquid retention. The materials of the resin or glass fiber separator include, but are not limited to, polyolefin, aromatic polyamide, polytetrafluoroethylene, polyethersulfone, and the like.

[0083] In one embodiment, the polyolefin is polyethylene or polypropylene. In some embodiments, the polyolefin is polypropylene. The materials of the above-mentioned diaphragm can be used alone or in any combination.

[0084] In one embodiment, the secondary battery may include an outer package, which can be used to encapsulate the electrode assembly and the electrolyte.

[0085] In one embodiment, the type of the electrolyte is not subject to specific restrictions. The electrolyte includes an electrolyte salt and an organic solvent. The specific types of the electrolyte salt and the organic solvent are not subject to specific restrictions and can be selected according to actual needs. The electrolyte may also include additives. The types of the additives are not particularly limited and may be film-forming additives for the positive electrode and / or the negative electrode, or additives that can improve certain battery properties, such as additives that improve high or low temperature performance of the battery.

[0086] In one embodiment, the outer packaging of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery can also be a soft package, such as a bag-type soft package. The material of the soft package can be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0087] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square, or any other shape.

[0088] An embodiment of the present application provides an electrical device, comprising the secondary battery described above.

[0089] Exemplarily, the above-mentioned electrical devices may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.

[0090] The following examples are provided to facilitate understanding of the present invention. These examples are not provided to limit the scope of the claims.

[0091] Example 1

[0092] A method for preparing a secondary battery comprises the following steps:

[0093] (1) Preparation of negative electrode active materials:

[0094] 1. The silicon negative electrode material and graphite are mixed evenly, wherein the silicon negative electrode is preferably silicon carbon, to obtain a mixture, the mixture is mixed evenly with polyacrylic acid, carboxymethyl cellulose, styrene-butadiene rubber and carbon nanotubes to obtain a precursor, the precursor is added with water to prepare a slurry with a solid content of 40%, atomized and granulated at 180°C, ball milled and sieved, and the first negative electrode active material and the second negative electrode active material are obtained respectively (by controlling the aperture size of the atomizer for atomization and granulation and the ball milling and sieving steps, the first negative electrode active material and the second negative electrode active material with different Dv50 can be obtained);

[0095] Among them, the mass ratio of silicon negative electrode material, graphite, polyacrylic acid, carboxymethyl cellulose, styrene-butadiene rubber and carbon nanotubes is 5:93:0.5:0.5:0.5:0.5.

[0096] (2) Preparation of negative electrode sheet: The first negative electrode active material, the second negative electrode active material and polytetrafluoroethylene are placed in a stirring barrel at a mass ratio of 15:80:5, and stirred according to the following stirring steps:

[0097] First, stir at 15°C, reverse (stirring paddle) 300 rpm, forward (barrel) 45 rpm, time 120 s;

[0098] Then stir at 15°C, reverse (stirring paddle) 2500 rpm, forward (barrel) 45 rpm, time 120 s;

[0099] Then stir at 65°C, reverse (stirring paddle) 5000 rpm, forward (barrel) 45 rpm, time 900 s;

[0100] The stirred material is passed through the roller gap with a speed difference of 0.7 between the upper and lower rollers at 120°C to form a membrane (the thickness of the membrane can be controlled by adjusting the number of times this step is repeated), and the thickness of the membrane is controlled to be 100μm;

[0101] The membrane was laminated onto a 8 μm copper foil current collector at 120° C. through the gap between upper and lower rollers at the same speed.

[0102] (3) Preparation of positive electrode sheet: The positive electrode active material lithium cobalt oxide is mixed with PVDF, carbon black SP (the mass ratio of lithium cobalt oxide, PVDF, carbon black SP is 8:1:1) and NMP to prepare a positive electrode slurry with a solid content of 70%. The positive electrode slurry is coated on a 9um aluminum foil to form a positive electrode sheet with a surface density of 19.48 mg / cm 2 .

[0103] (4) Diaphragm: The base membrane is a 16 μm PE diaphragm.

[0104] (5) Electrolyte: EC and DMC were mixed in a volume ratio of 1:1, and then lithium hexafluorophosphate was added in a glove box to prepare an electrolyte with a concentration of 1 mol / L.

[0105] (6) Assembly of secondary batteries: stack the positive electrode sheet, separator, and negative electrode sheet in order, with the separator placed between the positive and negative electrode sheets, and obtain a bare cell by winding, hot pressing, and welding the tabs. Place the bare cell in an outer packaging aluminum-plastic film and bake it in an oven at 85±10°C for 24 hours. Inject the above-prepared electrolyte into the dried battery, let it stand, form it, and separate the capacity to obtain a secondary battery.

[0106] The parameters of Example 1 are shown in Table 1.

[0107] Embodiments 2 to 5

[0108] The difference between Examples 2 to 5 and Example 1 is that the mass ratio of the first negative electrode active material, the second negative electrode active material and polytetrafluoroethylene is changed, thereby changing the value of C.

[0109] In Example 2, the mass ratio of the first negative electrode active material, the second negative electrode active material and polytetrafluoroethylene is 15:84.9:0.1.

[0110] In Example 3, the mass ratio of the first negative electrode active material, the second negative electrode active material and polytetrafluoroethylene is 15:83:2.

[0111] In Example 4, the mass ratio of the first negative electrode active material, the second negative electrode active material and polytetrafluoroethylene is 15:77:8.

[0112] In Example 5, the mass ratio of the first negative electrode active material, the second negative electrode active material and polytetrafluoroethylene is 15:75:10.

[0113] Embodiments 6 to 13

[0114] The difference between Examples 6 to 13 and Example 1 is that by controlling the aperture size of the atomizer for atomization granulation and the ball milling and screening steps, the first negative electrode active material and the second negative electrode active material with different Dv50 can be obtained, thereby changing A and / or B.

[0115] Embodiments 14 to 17

[0116] The difference between Examples 14 to 17 and Example 1 is that the value of N is adjusted by changing the thickness of the diaphragm.

[0117] Examples 18 to 21

[0118] The difference between Examples 18 to 21 and Example 1 is that the mass ratio of the first negative electrode active material, the second negative electrode active material and polytetrafluoroethylene is changed.

[0119] In Example 18, the mass ratio of the first negative electrode active material, the second negative electrode active material and polytetrafluoroethylene is 1:94:5.

[0120] In Example 19, the mass ratio of the first negative electrode active material, the second negative electrode active material and polytetrafluoroethylene is 10:85:5.

[0121] In Example 20, the mass ratio of the first negative electrode active material, the second negative electrode active material and polytetrafluoroethylene is 20:75:5.

[0122] In Example 21, the mass ratio of the first negative electrode active material, the second negative electrode active material and polytetrafluoroethylene is 30:65:5.

[0123] Embodiments 22 to 28

[0124] The difference between Examples 22 to 26 and Example 1 is that the mass ratio of silicon negative electrode material, graphite, polyacrylic acid, carboxymethyl cellulose, styrene-butadiene rubber, and carbon nanotubes is changed.

[0125] The mass ratio of the silicon negative electrode material, graphite, polyacrylic acid, carboxymethyl cellulose, styrene-butadiene rubber, and carbon nanotubes in Example 22 is 1:95:1:1:1:1.

[0126] The mass ratio of the silicon negative electrode material, graphite, polyacrylic acid, carboxymethyl cellulose, styrene-butadiene rubber, and carbon nanotubes in Example 23 is 2:94.8:0.8:0.8:0.8:0.8.

[0127] The mass ratio of the silicon negative electrode material, graphite, polyacrylic acid, carboxymethyl cellulose, styrene-butadiene rubber, and carbon nanotubes in Example 24 is 10:88.4:0.4:0.4:0.4:0.4.

[0128] The mass ratio of the silicon negative electrode material, graphite, polyacrylic acid, carboxymethyl cellulose, styrene-butadiene rubber, and carbon nanotubes in Example 25 is 20:79.2:0.2:0.2:0.2:0.2.

[0129] The mass ratio of the silicon negative electrode material, graphite, polyacrylic acid, carboxymethyl cellulose, styrene-butadiene rubber, and carbon nanotubes in Example 26 is 30:69.6:0.1:0.1:0.1:0.1.

[0130] The mass ratio of the silicon negative electrode material, graphite, polyacrylic acid, carboxymethyl cellulose, styrene-butadiene rubber, and carbon nanotubes in Example 27 is 20:79.2:0.8:0.0:0.0:0.0

[0131] The mass ratio of the silicon negative electrode material, graphite, polyacrylic acid, carboxymethyl cellulose, styrene-butadiene rubber, and carbon nanotubes in Example 28 is 20:79.2:0.0:0.8:0.0:0.0

[0132] The mass ratio of silicon negative electrode material, graphite, polyacrylic acid, carboxymethyl cellulose, styrene-butadiene rubber and carbon nanotubes in Example 29 is 20:79.2:0.4:0.2:0.2:0, and the conductive agent carbon nanotubes are added by dry stirring in the subsequent preparation step of the negative electrode plate.

[0133] Comparative Example 1

[0134] The difference between Comparative Example 1 and Example 1 is that by controlling the aperture size of the atomizer for atomization granulation and the ball milling and screening steps, the first negative electrode active material and the second negative electrode active material with different Dv50 can be obtained, thereby changing A and / or B.

[0135] Comparative Example 2

[0136] The difference between Comparative Example 2 and Example 1 is that the mass ratio of the first negative electrode active material, the second negative electrode active material and polytetrafluoroethylene is changed.

[0137] In Comparative Example 2, the mass ratio of the first negative electrode active material, the second negative electrode active material and polytetrafluoroethylene is 15:84.95:0.05.

[0138] Comparative Example 3

[0139] The difference between Comparative Example 3 and Example 1 is that Comparative Example 1 does not contain the first negative electrode active material.

[0140] The mass ratio of the second negative electrode active material and polytetrafluoroethylene in Comparative Example 3 is 95:5.

[0141] Comparative Example 4

[0142] The difference between Comparative Example 4 and Example 1 is that Comparative Example 4 does not contain the second negative electrode active material.

[0143] The first negative electrode active material, the second negative electrode active material and polytetrafluoroethylene are mixed in a mass ratio of 95:5.

[0144] Table 1

[0145]

[0146] Performance Testing

[0147] Cyclic test method & DCR test method: Environment: Temperature box configuration: Temperature 25°C, the specific steps are as follows:

[0148] Step 1: 0.2C discharge to 3.0V and let stand for 5 minutes;

[0149] Step 2: Charge at 0.5C to 4.5V, cut-off rate 0.02C, and let stand for 5 minutes;

[0150] Step 3: discharge at 1A constant current, 500ms, and let stand for 5min; Step 4: discharge at 0.2C to 3.0V and let stand for 5min;

[0151] Step 5: Charge at 0.5C to 4.5V, cut-off rate 0.02C, and let stand for 5 minutes;

[0152] Step 6: Discharge at 0.2C to 3.0V and let stand for 5 minutes. Record the discharge capacity as Cap0.

[0153] Step 7: Charge at 1.5C to 4.5V, cut-off rate 0.02C, and let stand for 5 minutes;

[0154] Step 8: 0.7C discharge to 3.0V and let stand for 5 minutes;

[0155] Step 9: Charge at 0.5C to 3.0V, cut-off rate 0.02C, and let stand for 5 minutes;

[0156] Step 10: Discharge at a constant current of 1A, 500ms, stand for 5min, and record DCR (1A-500ms);

[0157] Repeat steps 7-8 for a total of 800 times, with the capacity of each cycle being Cap1.

[0158] Calculate the capacity retention rate per cycle Cap1 / Cap.

[0159] Table 2

[0160]

[0161]

[0162] As can be seen from Table 2, the present application satisfies the following relationship by controlling the Dv50 particle size of the negative electrode active material in the first negative electrode active material, the second negative electrode active material, the grading ratio (X) of the negative electrode active material, the tensile strength of the negative electrode sheet and the content of the binder in the negative electrode active material layer: 0.69≤(A+B)*X / (N*C)≤160, which can effectively improve the adhesion and conductivity of the negative electrode sheet, effectively inhibit the expansion and contraction of the negative electrode active material, improve the ion conductivity of the negative electrode sheet, improve the dispersion effect of the binder, avoid its agglomeration, reduce the amount of lithium fluoride generated on the surface of the negative electrode sheet, and at the same time improve the stability of the negative electrode active material, avoid the powdering of the sheet, avoid its breakage during the preparation of the negative electrode sheet, increase the compaction density, promote the uniform distribution of the negative electrode active material on the negative electrode sheet, shorten the migration and diffusion path of the active ions in the negative electrode active material, effectively improve the first coulomb efficiency of the secondary battery, reduce the impedance, and improve the cycle performance.

[0163] By comparing Examples 2 and 12 with other examples, it can be seen that the present application can further reduce the impedance of the secondary battery and improve the cycle performance of the secondary battery by controlling 1.6≤(A+B)*X / (N*C)≤9.6.

[0164] It can be seen from the comparison of Examples 1 to 5 that by controlling 2≤C≤8, the cycle performance is further improved and the impedance is reduced.

[0165] By comparing Examples 1 and 6 to 8, it can be seen that by controlling 2≤A≤4, the cycle performance is further improved and the impedance is reduced.

[0166] By comparing Example 1 and Examples 9 to 11, it can be seen that by controlling 20≤B≤25, the cycle performance is further improved and the impedance is reduced.

[0167] By comparing Examples 1 and 14 to 17, it can be seen that by controlling 0.2≤N≤0.4, the cycle performance is further improved and the impedance is reduced.

[0168] By comparing Examples 1 and 18 to 21, it can be seen that by controlling 10≤D≤20 and 75≤E≤85, the cycle performance is further improved and the impedance is reduced.

[0169] By comparing Example 1 and Examples 24 to 26, it can be seen that by controlling the mass ratio of the silicon-based material, graphite, the second binder, and the conductive agent to (2 to 20): (79.2 to 94.8): (0.6 to 2.4): (0.0.2 to 0.8), the cycle performance is further improved and the impedance is reduced.

[0170] By comparing Examples 1, 27, 28 and 29, it can be seen that by controlling the mass ratio of the silicon-based material, graphite, the second binder and the conductive agent to (1-30): (69.4-95): (0.3-3): (0.1-1), the cycle performance is further improved and the impedance is reduced.

[0171] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A negative electrode plate, characterized in that: A negative electrode current collector and a negative electrode active material layer located on at least one surface of the negative electrode current collector, wherein the negative electrode active material layer includes a negative electrode active material and a first binder; The negative electrode active material includes a first negative electrode active material and a second negative electrode active material; The negative electrode sheet satisfies: 0.69≤(A+B)*X / (N*C)≤160, X=A / B; A μm is the Dv50 particle size of the first negative electrode active material; Bμm is the Dv50 particle size of the second negative electrode active material; N MPa is the tensile strength of the negative electrode plate; C% is the mass percentage of the first binder in the negative electrode active material layer.

2. The negative electrode sheet according to claim 1, characterized in that: Satisfy at least one of the following (1) to (5): (1)0.4≤A≤8; (2)10≤B≤45; (3)0.01≤X≤0.8; (4)0.1≤N≤0.5; (5)0.05≤C≤10。 3. The negative electrode sheet according to claim 1, characterized in that: The first binder includes at least one of polytetrafluoroethylene or its derivatives, polyvinylidene fluoride or its derivatives, carboxymethyl cellulose or its derivatives, nitrocellulose or its derivatives, styrene-butadiene rubber or its derivatives, nitrile rubber or its derivatives, and polyacrylic acid or its derivatives.

4. The negative electrode sheet according to claim 1, characterized in that: The mass percentage of the first negative electrode active material in the negative electrode active material layer is D, 1%≤D≤30%; and / or The mass percentage of the second negative electrode active material in the negative electrode active material layer is E, and 60%≤E≤98.9%.

5. The negative electrode sheet according to claim 1, characterized in that: The negative electrode active material includes a core and a coating layer arranged on the outer surface of the core, the core includes a silicon-based material and graphite, and the coating layer includes a second binder and a conductive agent; the mass ratio of the silicon-based material, graphite, second binder, and conductive agent is (1-30): (69.4-95): (0.3-3): (0.1-1).

6. The negative electrode sheet according to claim 5, characterized in that: The coating layer includes polyacrylic acid or its derivatives, styrene-butadiene rubber or its derivatives, carboxymethyl cellulose or its derivatives, and a conductive agent; the mass ratio of the silicon-based material, graphite, polyacrylic acid or its derivatives, styrene-butadiene rubber or its derivatives, carboxymethyl cellulose or its derivatives, and the conductive agent is (1-30): (69.4-95): (0.1-1): (0.1-1): (0.1-1): (0.1-1).

7. The negative electrode sheet according to claim 5, characterized in that: The silicon-based material includes at least one of silicon-oxygen material, silicon-carbon material, and nano-silicon.

8. The negative electrode sheet according to claim 5, characterized in that: The conductive agent includes at least one of carbon nanotubes, carbon black, carbon dots, graphene, and carbon nanofibers.

9. The negative electrode sheet according to claim 5, characterized in that: The second binder includes at least one of polytetrafluoroethylene or its derivatives, polyvinylidene fluoride or its derivatives, carboxymethyl cellulose or its derivatives, nitrocellulose or its derivatives, styrene-butadiene rubber or its derivatives, nitrile rubber or its derivatives, and polyacrylic acid or its derivatives.

10. A secondary battery, characterized in that: It comprises the negative electrode sheet as described in any one of claims 1 to 9.

11. An electrical device, characterized in that: The secondary battery according to claim 10 is included.

Citation Information

Patent Citations

  • Anode for secondary battery, and lithium secondary battery manufactured therefrom

    CN106257713A

  • Electrochemical device and electronic device

    CN114665066A

  • Battery

    CN119008939A

  • Negative electrode material for lithium ion secondary battery, negative electrode for lithium ion secondary battery, and lithium ion secondary battery

    JP2012151088A

  • Display device and method of driving the same

    KR1020220163554A

Cited By

  • Composite negative electrode and preparation method and application thereof

    CN121097025A